Plasmodium falciparum Resistance to Artemisinin Derivatives and Piperaquine: A Major Challenge for Malaria Elimination in Cambodia - Duru, Valentine (Am J Trop Med Hyg, 2016)
Artemisinin-based combination therapies (ACTs) are the cornerstone of current strategies for fighting malaria. Over the last decade, ACTs have played a major role in decreasing malaria burden. However, this progress is being jeopardized by the emergence of artemisinin-resistant Plasmodium falciparum parasites. Artemisinin resistance was first detected in western Cambodia in 2008 and has since been observed in neighboring countries in southeast Asia. The problem of antimalarial drug resistance has recently worsened in Cambodia, with reports of parasites resistant to piperaquine, the latest generation of partner drug used in combination with dihydroartemisinin, leading to worrying rates of clinical treatment failure. The monitoring and the comprehension of both types of resistance are crucial to prevent the spread of multidrug-resistant parasites outside southeast Asia, and particularly to Africa, where the public health consequences would be catastrophic. To this end, new tools are required for studying the biological and molecular mechanisms underlying resistance to antimalarial drugs and for monitoring the geographic distribution of the resistant parasites. In this review, we detail the major advances in our understanding of resistance to artemisinin and piperaquine and define the challenges that the malaria community will have to face in the coming years.